Pelaksanaan Penyerahan Protokol Notaris yang Pensiun dengan Permintaan Sendiri Berdasarkan Undang-Undang Jabatan Notaris Serta Implementasi di Kota Padang dan Padang Pariaman - Syahrul, Reski Novita; Fendri, Azmi; Delfiyanti, Delfiyanti (UNES Law Review, 2023)
Notary is a public official who has the authority to make authentic deeds and has other authorities as defined in this Law or based on other Laws. Notary is a position that has been regulated in the Legislation. However, there are times when a notary will end his term of office either by stopping at his own request and in the UUJN it is also stated that a notary who stops at his own request must report to the MPD and indicate who will be a substitute Notary for submitting the protocol. The method used in this thesis is an empirical research method. In this research, an understanding was obtained that if a notary stops at his own request, all protocols will be submitted to a replacement notary and appointed by the MPD. However, in the implementation that occurred in the cities of Padang and Padang Pariaman, the handover began with a Notary who stopped at his own request and was notified to the MPD that the MPD would process a letter from the Indonesian Ministry of Law and Human Rights. In its implementation, submission of notary protocols in the cities of Padang and Padang Pariaman did not go smoothly. Due to time delays in the process of issuing ministerial decrees, the handover of the notary protocol to a replacement notary is delayed and does not comply with the time period allowed according to UUJN. As long as there is no such decision, the notary cannot issue a copy of the deed for those who need it. However, in practice in the cities of Padang and Padang Pariaman these obstacles can be overcome by providing understanding to the parties or notaries who will retire.